Sensitivity of conformation sensitive gel electrophoresis in detecting mutations in Marfan syndrome and related conditions. Issue 1 (1st January 2002) - Körkkö, J; Kaitila, I; Lönnqvist, L; Peltonen, L; Ala-Kokko, L
Abstract : Objective: It has been firmly established that mutations in the gene for fibrillin 1, FBN1, cause Marfan syndrome (MFS). FBN1 mutations can also cause other phenotypes, such as ectopia lentis (EL) and familial isolated thoracic aortic aneurysm and dissection (FAA). When the clinical presentation is typical, diagnosis of MFS is usually easy to make. However, there can be a marked phenotypic variation between affected subjects even in one family, and making the diagnosis can be challenging, especially in childhood. The objective of this study was to test the sensitivity of conformation sensitive gel electrophoresis (CSGE) for detecting mutations in FBN1 in MFS and related phenotypes. Design: Setting up CSGE analysis for the FBN1 gene and testing the method first by screening coded samples from 17 MFS patients with previously detected FBN1 mutations. We then used a test set consisting of 46 coded samples representing MFS, related phenotypes, and controls. Results: Sixteen of the 17 known mutations were detected. Altogether 23 mutations were detected in a test set consisting of 46 coded samples representing MFS, related phenotypes, and controls. Nineteen of the mutations were novel. The mutation was detected in 18 of the 20 MFS patients and in one patient with familial EL, but not in a patient with sporadic MASS syndrome, any of the five sporadic annuloaortic ectasia (AAE) patients, or any of the 15 controls. A FBN1 mutation was detected in four members of a multigeneration family with AAE, however. Conclusions: These results indicate that CSGE is highly sensitive for the detection of mutations in FBN1, and that molecular diagnostics is a useful means of confirming clinical diagnoses of MFS and related disorders. Further careful investigations are needed, however, in order to correlate the interfamilial and intrafamilial clinical variabilities of fibrillinopathies and mutations in FBN1 .